PENGARUH GROWTH SALES, SALES To CURRENT ASSET (SALCA), DAN RETAINED EARNINGS To TOTAL ASSET (RETA) TERHADA HARGA SAHAM PADA SEKTOR ANEKA INDUSTRI DI BURSA EFEK INDONESIA (BEI) - B51110046, ERNI JUITA (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
This study aims to analyze the influence of Growth Sales, Sales to Current Assets, and Retained Earnings to Total Assets on stock prices. Metodology research as the sample using purposive sampling. This study using a sample of 20 companies various industry sectors listed on the IDX in 2012-2014. Variables used in these study were, Stock Prices as the dependent variable the Growth Sales, Sales to Current Assets and Retained Earnings to Total Assets as in independent variable. The analyze method used is multiple regression analysis previously performed classical assumption, and then lastly using the F test, T test and R test. The results of  T test, can be seen that Retained Earnings to Total Assets have significant positive effect on stock prices, while variable Growth Sales, and Sales to Current Asset haven’t significant negative effect on stock prices. The result of F test on shows that the three variables simultaneously influential on stock prices. Prediction capability from these three variables on stock prices is 10.3% where the belence 89.7% is influenced by other factors not included into the research model. Keywords            :Stock Prices, Growth Sales, Sales to Current Assets, and Retained Earnings to Total Assets.